Legal Protection to the Auction Winner with Good Intentions of Mortgage Rights on Grosse Minutes of Auction Number 780/14/2019 - Ade Muhammad Syamkirana Putra; Siti Kunarti (Kosmik Hukum, 2022)
The government has provided legal protection to auction winners who take part in the auction with good intentions and in line with the rules, including those that are specifically regulated in the Regulation of the Minister of Finance Number 27/PMK.06/2016 concerning Auction Implementation Guidelines. The auction winner of Grosse Minutes of Auction Number: 780/44/2019 felt helpless and burdened by not being able to own the tangible object of what he purchased in the auction because the previous owner or mortgage giver objected to emptying the tangible object voluntarily. This problem made the auction winner burdened to forcibly vacate the tangible object from the auction he won and results in new legal actions. This research was conducted through library research to collect secondary data from primary, secondary, and tertiary legal sources. The owner of the Grosse Minutes of Auction number 780/44/2019, who won this auction and had good intentions, should be provided legal protection. This is done to uphold the principles of justice and give the auction winner legal security over his ownership of the tangible auction objects (land and building) that had been purchased. Article 1977, paragraph 1, of the Civil Code (hereafter referred to as the Civil Code) provides legal protection for purchasers who have good intentions. In essence, this article protects purchasers of movable property. According to Article 1977, paragraph 1 of the Civil Code, whoever controls movable property that is not in the form of interest and receivables that are not required to be paid to the bearer is declared to be the ownerKeywords: Legal Protection, Auction Winner, Grosse Minutes of Auction